Respostas cicatricial e à ventilação mecânica de transplantes de traquéia autólogo e homógeno em coelhos - Guimarães, Roberto Salvador de Souza (2006)
The purpose of this paper was to study the cicatricial behavior and response to the intraoperatory mechanical ventilation of the transplanted segment of trachea (autologous and homologous transplant of the entire segment) in rabbits The Qui-square test showed no significant statistical difference between the groups studied However there was a higher weight loss in Group II With regard to survival time the Qui-square test (p<0.05) revealed that the averages were considered statistically different (tc = - 3.60) and survival of Group I was longer than that of Group II Direct necroscopy and radiological evaluation using the Kruskall-Wallis test (p<0.05) showed no statistical difference between the groups Complications such as stenosi formation of granulomas and fistulas were observed in both groups With regard to intraoperatory behavior and response to mechanical ventilation the Kruskall-Wallis test (p<0.05) showed no significant statistical difference between the Groups I and II Both groups exhibited good resistance to the high pressure of the intraoperatory mechanical ventilation Using the Kruskall-Wallis test no significant statistical differences was observed between the groups concerning the anatomopathological results In Group I there was a higher prevalence of granuloma bone metaplasia necrosis in the region of the anastomosis fibroplasia reepithelialization of the graft and polymorfonuclear infiltration Inflammatory reactions predominantly chronic were similar in both groups Cicatrization occurred with the same frequency in the both groups Reepitelization and early and late inflammatory reactions were observed in both groups but the animals with autologous transplant had a better clinical evolution and survived for a longer time than those which received a homologous transplant